Stem cells: a revolution in regenerative medicine - Lidyce Quesada Leyva; Cira Cecilia León Ramentol; Sandra Fernández Torres; Elizabeth Nicolau Pestana (Centro Provincial de Información de Ciencias Médicas, 2017)
Advances in regenerative medicine have been evident in the last years  and this has been obtained due to the new knowledge related to stem cells, which use in the replacement therapy has given rise to a new age in medicine. To such effects, a literature review was carried out aimed at spreading its generalities and implementations, as well as everything related to the basic investigations carried out in this field and the main achievements obtained. The possibility of expansion and differentiation of such cells, allow to obtain enough quantitiy of them, which helps the development of cell therapy.